LOMLOE, an opportunity for curricular modernization - Coll Salvador, César; Martín Ortega, Elena (Avances en Supervisión Educativa, 2021)
The article reflects on the opportunity that LOMLOE and its development represent for the curricular modernization of our educational system. The role played by the curriculum, the importance of knowing the educational intentions and the guidelines to promote learning and organize teaching are analyzed. The new learning requirements are exposed and some options and criteria are presented that should be taken into account in the process of curricular modernization, taking into account, on the one hand, the exit profile of the students, which takes as a reference the eight key competences and the major challenges of the 21st century and, on the other hand, to the essential learning of the specific competences of the areas and subjects, differentiating between essential basic learning and desirable basic learning, emphasizing that the goal of learning is not the content but the basic skills.Finally, the importance of good policies for adequate curricular development and collaboration between the Ministry and the autonomous communities is pointed out, highlighting that the challenge of equity needs to provide sufficient curricular autonomy to the centers so that they can expand and deepen certain contents and even address others based on the diversity of student profiles, in line with the new proposals for personalizing learning.
Keywords: basic skills; challenges of the 21st century; curriculum; essential learning; equity; LOMLOE; personalization of learning